Relationships between Euglobulin Clot Lysis Time and the Plasma Levels of Tissue Plasminogen Activator and Plasminogen Activator Inhibitor 1 - Urano, Tetsumei; Sakakibara, Kenji; Rydzewski, Andrzej; Urano, Shoko; Takada, Yumiko; Takada, Akikazu (Thrombosis and Haemostasis, 1990)
The relationships between tissue plasminogen activator (tPA), its fast acting inhibitor (PAI-1) and euglobulin clot lysis time (ELT) were investigated with healthy volunteers’ plasma. Turbidimetric clot lysis assay by the microtiter plate reader was utilized for ELT with a slight modification. Both tPA and PAI-1 showed the significant correlation with ELT. tPA had a significantly positive, not negative, correlation with ELT (R = 0.387, p <0.001). Higher correlation coefficients (R = 0.580, p <0.001 and R = 0.599, p <0.001) were obtained between ELT and total PAI-1 or free PAI-1 than tPA or tPA-PAI-1 complex (R = 0.427, p <0.001). The positive correlation was also obtained between tPA and PAI-1. These data suggest that PAI-1 is a highly important factor for ELT, especially, the amounts of free PAI-1 being the key factor to determine the ELT, which can represent the potential activity of the fibrinolytic system.
Keywords: Euglobulin clot lysis time; Tissue plasminogen activator; Plasminogen activator inhibitor 1